Welcome to the Meta(l)verse: ,,Virtual Metal“ – Welche Chancen und Herausforderungen ergeben sich für Metal und Metal-Festivals im virtuellen Raum - Andreas Wagener (Menschen, Marken, Moshpits: Wirtschaftliche und kommunikative Aspekte von Open-Air-Veranstaltungen am Beispiel von Metal-Festivals in Deutschland, 2025)
The term “metaverse” describes the merging of the virtual and physical world. The underlying technical development leads to a change in market conditions and should enable new business models – also in the area of the festival economy. The text is dedicated to the opportunities and challenges that the metaverse opens up for the event and music industry, especially for the metal segment and respective festivals. The article approaches the topic conceptually, on the basis of an ethnographic analysis of use cases, whose transferability to this context is examined. It is shown that the staging of live music in the field of metal in virtual space is currently only possible with a loss of festival flair and entertainment quality, at least if conventional “physical” festival experiences are taken as yardstick. However, there is potential in the distribution of virtual goods and the utilisation of digital services as an extension of the value chain of concert events and festivals. All in all, a media-adequate staging and the appropriate use of relevant instruments of the virtual sphere are needed to be successful in this context.
Keywords: 650; Metaverse; NFTs; Digitalisierung; Virtual Reality; VR; Heavy Metal; Festival